Phytochemical Screening, Antioxidant Activity, And Antimitotic Potential Of Shallot Skin (Allium Cepa L.) Extract - Raisa Fadilla; Maryam Jamila Arief; Satriani Badawi; Venna Sinthary; Putri Anggreini; Leny Eka Tyas Wahyuni; Nur Rezky Khairun Nisa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Shallot skin (Allium cepa L.) is a by-product that is generally discarded as household waste, despite its potential as a source of bioactive compounds. Previous studies have indicated that shallot skin contains secondary metabolites with antioxidant and cytotoxic properties. This study aimed to evaluate the phytochemical composition, antioxidant activity, and antimitotic potential of shallot skin extract in order to support its valorization as a natural bioactive resource. Materials and methods. This research was conducted as an experimental laboratory study. Dried shallot skin was extracted using ethanol through a maceration method, followed by solvent evaporation to obtain a crude extract. Phytochemical screening was performed using Thin Layer Chromatography (TLC) to identify major secondary metabolites. Solvent partitioning was carried out using n-hexane and ethyl acetate, and further fractionation was conducted using vacuum column chromatography and preparative TLC. Antioxidant activity was evaluated using the DPPH radical scavenging assay, while antimitotic activity was assessed using the Brine Shrimp Lethality Test (BSLT). Results. The ethanolic extraction produced a high yield of crude extract (57.13%), indicating effective recovery of polar and semi-polar compounds. Phytochemical screening confirmed the presence of alkaloids, flavonoids, and phenolic compounds. The extract exhibited very strong antioxidant activity with an IC₅₀ value of 17.477 µg/mL. Antimitotic evaluation using BSLT showed an LC₅₀ value of 202.301 µg/mL, indicating biological activity at moderate concentrations. Conclusions. The findings demonstrate that shallot skin contains diverse secondary metabolites with strong antioxidant activity and measurable antimitotic potential. These results support the utilization of shallot skin as a valuable natural source of bioactive compounds and provide a basis for further studies on compound isolation and advanced biological evaluation.